Reflexiones sobre la conexión Cerdeña-Huelva con motivo de un nuevo jarro ascoide sardo - González de Canales Cerisola, Fernando; Serrano Pichardo, Leonardo; Llompart Gómez, Jorge (Madrider Mitteilungen, 2020)
Zusammenfassung folgt.